Book Reviews (The Muslim world, 1951)
Book reviews in this article: The Unveiling. By Grace Visher Payne The Christian Church and Missions in Ethiopia (including Eritrea and the Somalilands). By J. Spencer Trimingham The Worlds Religions. Edited by J. N. D. Anderson India, Pakistan, Ceylon. Edited by W. Norman Brown Ancient West Arabian. By Chaim Rabin Arabic Grammar: Inductive Method. By E. E. Elder Woordenboek Bahasa Indonesia—Nederlands. By H. D. Van Pernis Indonesisch—Nederlands Woordenboek. By W. J, S. Poerwadarminta and Dr. A. Teeuw Bahasa Indonesia, The National Language of Indonesia. A Course for English-Speaking Students. By E. Pino Le Coran. Traduction selon un essai de reclassement des sourates. By Régis Blachère Acta Orientalia Academiae Scientiarum Hungaricae. redigit L. Ligeti. Tomus I Mystique naturelle et mystique surnaturelle en Islam. Par Louis Gardet Quelques textes Sufis concernant l' “extase.” Par Louis Gardet Alfarabi, la statistique des Sciences: texte établi, annoté et présenté par Osman Amine. Le Caire Der Islam in der neuen Turkei; eine rechtsgeschichtliche Untersuchung. Von Gotthard Jäschke Islam in the Modern World. Addresses at the Fifth Annual Conference on Mid-dle East Affairs I Married An Arab. By Mary Winifred Bushakra